Perkembangan Kerajaan Allah Zaman Paulus - Lukas Thelios Rangin; Jen Katrin Enok; Sinta Pembriani; Sarmauli Sarmauli (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This paper analyzes the development of the concept of the Kingdom of God in the teachings of the Apostle Paul based on his letters. The Kingdom of God is understood not only as an eschatological reality that will be fully realized at the second coming of Christ, but also as a spiritual reality that is already present today through the saving work of Christ and led by the Holy Spirit. Paul emphasizes the duality of the Kingdom of God as a reality that is already possessed by believers and a hope for its fulfillment in the future. This study also examines the social, political, and cultural factors in the Roman era that influenced the spread of the teachings of the Kingdom of God developed by Paul. This study makes an important contribution to the understanding of eschatological theology and Christian ethics and their implications for the lives of believers at that time and today.